The Christian Brethren as the nineties began - Brierley, Peter; Partnership; Howden, Harold H. (Carlisle, UK Paternoster, 1993)
Includes bibliographical references.
Results of the 1988 survey on the nature of Christian Brethren congregations in the British Isles.
Keywords: Brethren movement -- church history -- 20th century -- Great Britain